Lysophosphatidic acid receptor1/3 antagonist inhibits the activation of satellite glial cells and reduces acute nociceptive responses. Issue 4 (26th February 2022) - Hoshino, Yoko; Okuno, Toshiaki; Saigusa, Daisuke; Kano, Kuniyuki; Yamamoto, Shota; Shindou, Hideo; Aoki, Junken; Uchida, Kanji; Yokomizo, Takehiko; Ito, Nobuko
Abstract: Lysophosphatidic acid (LPA) exerts various biological activities through six characterized G protein‐coupled receptors (LPA1‐6 ). While LPA–LPA1  signaling contributes toward the demyelination and retraction of C‐fiber and induces neuropathic pain, the effects of LPA–LPA1  signaling on acute nociceptive pain is uncertain. This study investigated the role of LPA–LPA1  signaling in acute nociceptive pain using the formalin test. The pharmacological inhibition of the LPA–LPA1 axis significantly attenuated formalin‐induced nociceptive behavior. The LPA1  mRNA was expressed in satellite glial cells (SGCs) in dorsal root ganglion (DRG) and was particularly abundant in SGCs surrounding large DRG neurons, which express neurofilament 200. Treatment with LPA1/3 receptor (LPA1/3 ) antagonist inhibited the upregulation of glial markers and inflammatory cytokines in DRG following formalin injection. The LPA1/3 antagonist also attenuated phosphorylation of extracellular signal‐regulated kinase, especially in SGCs and cyclic AMP response element‐binding protein in the dorsal horn following formalin injection. LPA amounts after formalin injection to the footpad were quantified by liquid chromatography/tandem mass spectrometry, and LPA levels were found to be increased in the innervated DRGs. Our results indicate that LPA produced in the innervated DRGs promotes the activation of SGCs through LPA1, increases the sensitivity of primary neurons, and modulates pain behavior. These results facilitate our understanding of the pathology of acute nociceptive pain and demonstrate the possibility of the LPA1 on SGCs as a novel target for acute pain control.